2016
DOI: 10.1186/s13613-016-0169-x
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol delivery with two ventilation modes during mechanical ventilation: a randomized study

Abstract: BackgroundVolume-controlled ventilation has been suggested to optimize lung deposition during nebulization although promoting spontaneous ventilation is targeted to avoid ventilator-induced diaphragmatic dysfunction. Comparing topographic aerosol lung deposition during volume-controlled ventilation and spontaneous ventilation in pressure support has never been performed. The aim of this study was to compare lung deposition of a radiolabeled aerosol generated with a vibrating-mesh nebulizer during invasive mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 37 publications
8
69
0
Order By: Relevance
“…A nebulizer operating continuously during both insufflation and expiration should be placed in the inspiratory limb, 15–40 cm upstream of the Y -piece [ 11 , 17 ]. The optimal distance from the Y -piece depends on bias flow and the circuit section.…”
Section: Practical Constraints To Optimizing Nebulized Antibiotic Delmentioning
confidence: 99%
See 1 more Smart Citation
“…A nebulizer operating continuously during both insufflation and expiration should be placed in the inspiratory limb, 15–40 cm upstream of the Y -piece [ 11 , 17 ]. The optimal distance from the Y -piece depends on bias flow and the circuit section.…”
Section: Practical Constraints To Optimizing Nebulized Antibiotic Delmentioning
confidence: 99%
“…Ventilator settings that enhance nebulization efficacy include a low respiratory frequency, low inspiratory flow and increased inspiratory time [ 14 , 26 ]. Volume-controlled ventilation with constant low inspiratory flow increases efficacy compared to pressure-controlled ventilation (high peak flow followed by deceleration) [ 17 , 27 ]. An end inspiratory pause may facilitate the settling of aerosol particles in the lung [ 26 ].…”
Section: Practical Constraints To Optimizing Nebulized Antibiotic Delmentioning
confidence: 99%
“…[16] Third, to optimize the drug delivery and to improve the deposition of amikacin particles in the deep lung tissue, a nebulization procedure protocol including operational specification, nebulizer type, drug formulation, and ventilator settings were optimized and standardized before the beginning of this study and carefully followed up during the study. [1718192021] We believed that these three improvements make our results to be a better evaluation of the therapeutic effects of AA on VAP caused by MDR-GNB.…”
Section: Discussionmentioning
confidence: 98%
“…The in vitro particle sizing study showed that 99% particles were in the 1-5 µm size range. This could be one of the reasons for better penetration compared to that reported for DTPA and 99m Tc labelled human serum albumin (0.32 to 0.75) [280,285]. The correlation with actual drug concentrations will need to be investigated with further studies using other techniques.…”
Section: Scintigraphic Assessment Of Lung Depositionmentioning
confidence: 92%
“…For the aerosol deposition, this right-left lung asymmetry is in keeping with the findings in experimental settings [286,287] and is likely due to airway geometry and the interaction between aerosol particles and airflow, called the Stokes number. Other studies have reported a right preponderance for lung deposition of DTPA with a wide variability in deposition between the lungs [285]. One reason for the variations in the distribution could be the effect of formulation and physicochemical properties of the aerosol on the deposition preference [182].…”
Section: Scintigraphic Assessment Of Lung Depositionmentioning
confidence: 96%